Massimo Pigliucci, Nonsense on Stilts - Marvan, Tomáš (Teorie vědy / Theory of Science, 2012)
Recenze / Review: Massimo PIGLIUCCI, Nonsense on Stilts: How to Tell Science from Bunk. Chicago: University of Chicago Press 2010, 332 s.